2009
DOI: 10.1021/bi900640x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Plasticity-Relevant Fucose-α(1−2)-Galactose Proteome from the Mouse Olfactory Bulb

Abstract: Fucose-α(1−2)-galactose [Fucα(1−2)Gal] sugars have been implicated in the molecular mechanisms that underlie neuronal development, learning, and memory. However, an understanding of their precise roles has been hampered by a lack of information regarding Fucα(1−2)Gal glycoproteins. Here, we report the first proteomic studies of this plasticity-relevant epitope. We identify five classes of putative Fucα(1−2)Gal glycoproteins: cell adhesion molecules, ion channels and solute carriers/transporters, ATP-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 63 publications
5
45
0
Order By: Relevance
“…The inhibition of ␣1-2-fucosylation caused by 2-deoxy-D-galactose incorporation delays neurite outgrowth and synaptic plasticity in the rat hippocampus (29,30). Mice that are deficient in FUT1 exhibit developmental defects in neurons that express NCAM in the OB (25). We showed that the abundance of ␣1-2Fuc glycan fluctuates in the lateral olfactory tract, which mostly contains axons of secondary olfactory neurons.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The inhibition of ␣1-2-fucosylation caused by 2-deoxy-D-galactose incorporation delays neurite outgrowth and synaptic plasticity in the rat hippocampus (29,30). Mice that are deficient in FUT1 exhibit developmental defects in neurons that express NCAM in the OB (25). We showed that the abundance of ␣1-2Fuc glycan fluctuates in the lateral olfactory tract, which mostly contains axons of secondary olfactory neurons.…”
Section: Discussionmentioning
confidence: 77%
“…Murrey et al (25) found using UEA-I affinity chromatography that 32 proteins including NCAM are ␣1-2-fucosylated in the OB, and Pestean et al (26) reported that NCAM is the main glycoprotein with ␣1-2Fuc glycan in the OB. We showed that the abundance of ␣1-2Fuc glycan associated with NCAM is diurnal, although the expression of Ncam1 mRNA and NCAM protein does not vary.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal functions, such as learning and memory, as well as neuronal morphological changes, including neurite outgrowth and synaptic plasticity are mediated by α1-2 fucose (α1-2Fuc) glycan [Pohle et al, 1987;Krug et al, 1991Krug et al, , 1994Matthies et al, 1996;Lorenzini et al, 1997;Kalovidouris et al, 2005;Murrey et al, 2006]. Murrey et al [2009] found that development of the olfactory bulb is defective in mice with a deficiency of α1-2-specific fucosyltransferase 1, and we recently showed that the amount of α1-2Fuc glycan in the olfactory bulb diurnally fluctuates via rhythmic expression of the Fut1 gene [Kondoh et al, 2014]. Therefore, α1-2Fuc glycan might control functional changes in the olfactory system during developmental stages and circadian variations.…”
mentioning
confidence: 99%
“…Although α1-2Fuc glycan has been histochemically localized in the mouse olfactory system using Ulex europaeus agglutinin-I (UEA-I) [Lundh et al, 1989;Ducray et al, 1999;Salazar et al, 2001;Lipscomb et al, 2002Lipscomb et al, , 2003Salazar and Sánchez Quinteiro, 2003;Murrey et al, 2009;Barrios et al, 2014;Kondoh et al, 2014], the findings are diverse. For example, we showed that α1-2Fuc glycan preferentially locates in the LOT and in the glomerular layer of the AOB of the ICR mouse [Kondoh et al, 2014] whereas other study groups have not found that UEA-I reacts with the mouse LOT.…”
mentioning
confidence: 99%
“…Likewise to the lectin-based approaches for the characterization of the O-and N-linked glycoproteomes, Murrey et al (165) used a more L-fucose-specific lectin from Ulex europaeus to enrich for fucosylated protein from different brain regions of adult and P3 mice. The 32 identified candidates belong to the classes of cell adhesion molecules, ion channels and solute carriers/transporters, ATP-binding proteins, synaptic-vesicle associated proteins and mitochondrial proteins, and most of them are predominantly expressed and developmentally regulated in the olfactory bulb.…”
Section: An Integrative View Of the Molecular Dynamics Of The Synapsementioning
confidence: 99%